Immunogenicity of WHO-17D and Brazilian 17DD yellow fever vaccines: a randomized trial - Camacho Luiz Antonio Bastos; Freire Marcos da Silva; Leal Maria da Luz Fernandes; Aguiar Savitri Gomes de; Nascimento Jussara Pereira do; Iguchi Takumi; Lozana José de Azevedo; Farias Roberto Henrique Guedes (Universidade de São Paulo, 2004)
OBJECTIVE: To compare the immunogenicity of three yellow fever vaccines from WHO-17D and Brazilian 17DD substrains (different seed-lots). METHODS: An equivalence trial was carried out involving 1,087 adults in Rio de Janeiro. Vaccines produced by Bio-Manguinhos, Fiocruz (Rio de Janeiro, Brazil) were administered following standardized procedures adapted to allow blocked randomized allocation of participants to coded vaccine types (double-blind). Neutralizing yellow fever antibody titters were compared in pre- and post-immunization serum samples. Equivalence was defined as a difference of no more than five percentage points in seroconversion rates, and ratio between Geometric Mean Titters (GMT) higher than 0.67. RESULTS: Seroconversion rates were 98% or higher among subjects previously seronegative, and 90% or more of the total cohort of vaccinees, including those previously seropositive. Differences in seroconversion ranged from -0.05% to -3.02%. The intensity of the immune response was also very similar across vaccines: 14.5 to 18.6 IU/mL. GMT ratios ranged from 0.78 to 0.93. Taking the placebo group into account, the vaccines explained 93% of seroconversion. Viremia was detected in 2.7% of vaccinated subjects from Day 3 to Day 7. CONCLUSIONS: The equivalent immunogenicity of yellow fever vaccines from the 17D and 17DD substrains was demonstrated for the first time in placebo-controlled double-blind randomized trial. The study completed the clinical validation process of a new vaccine seed-lot, provided evidence for use of alternative attenuated virus substrains in vaccine production for a major manufacturer, and for the utilization of the 17DD vaccine in other countries.